Lipid peroxidation biomarkers associated with height and obesity measures in the opposite direction in women. Issue 6 (26th April 2022) - Li, Mengjie; Zhao, Yingya; Dai, Qi; Milne, Ginger; Long, Jirong; Cai, Qiuyin; Chen, Qingxia; Zhang, Xianglan; Lan, Qing; Rothman, Nathaniel; Gao, Yu‐Tang; Shu, Xiao‐Ou; et al.
Abstract: Objective: This study aimed to investigate whether and how lipid peroxidation markers are associated with height and obesity measures. Methods: In two independent samples of women (Study 1: n = 1, 005; Study 2: n  = 1, 158), systemic levels of lipid peroxidation were assessed by urinary markers F2 ‐isoprostanes (F2 ‐IsoPs) and its major metabolite (F2 ‐IsoP‐M), with gas chromatography/negative ion chemical ionization mass spectrometry assays. Anthropometric parameters were directly measured and genetically estimated, and they were used in the primary analysis and in a Mendelian randomization analysis in relation to lipid peroxidation, respectively, with general linear models. Results: After adjusting for potential confounders, it was found that measured adult height was inversely associated with levels of F2 ‐IsoPs ( β = −0.89, p < 0.001) and F2 ‐IsoP‐M ( β = −0.71, p = 0.003), whereas obesity measures were positively associated with F2 ‐IsoP‐M ( β = 1.81, p < 0.001 for BMI; and β = 0.77, p < 0.001 for waist circumference). Results were consistent between the two study samples. The opposite associations were further replicated when using genetically determined measures of height and obesity in the Mendelian randomization analysis. Moreover, analyses mutually adjusted for height and obesity measures suggested that these associations were independent of one another. Conclusions: This study, for the first time, to our knowledge, reveals that a shared biological process (lipid peroxidation) is associated with both height and obesity measures but in the opposite direction.